Advantages Of Using Mobile Applications In The Educational Process (Eurasian Journal of Media and Communications, 2024)
This article highlights the possibilities of using mobile applications by professors and teachers of higher education when preparing students for professional activities. Also today, there are online and offline software tools for creating mobile applications, and the study highlights the capabilities of programs such as Android Studio, Zoho Creator, Quixy, AppMySite, iBuildApp.